2008
DOI: 10.1111/j.1745-6584.2008.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Stream Bottom Resistivity Tomography to Map Ground Water Discharge

Abstract: This study investigates the effectiveness of direct current electrical resistivity as a tool for assessing ground water/surface water interactions within streams. This research has shown that patterns of ground water discharge can be mapped at the meter scale, which is important for understanding stream water quality and ecosystem function. Underwater electrical resistivity surveys along a 107-m stream section within the Burd Run Watershed in South Central Pennsylvania identified three resistivity layers: a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 31 publications
4
53
0
1
Order By: Relevance
“…Nyquist et al [38] identified three resistivity layers in similar settings: a resistive (100 to 400 Ωm) surface layer corresponding to the streambed sediments, a conductive (20 to 100 Ωm) middle layer corresponding to residual clay sediments, and (unrelated to the current case study) a resistive (100 to 450 Ωm) bottom layer corresponding to the carbonate bedrock. Crook et al [39] could show that, for similar settings, the boundary between the lower two resistivity regions correlates well with the interface previously logged between the alluvial gravels (95 to 1500 Ωm) and underlying weathered limestone (10 to 75 Ωm).…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…Nyquist et al [38] identified three resistivity layers in similar settings: a resistive (100 to 400 Ωm) surface layer corresponding to the streambed sediments, a conductive (20 to 100 Ωm) middle layer corresponding to residual clay sediments, and (unrelated to the current case study) a resistive (100 to 450 Ωm) bottom layer corresponding to the carbonate bedrock. Crook et al [39] could show that, for similar settings, the boundary between the lower two resistivity regions correlates well with the interface previously logged between the alluvial gravels (95 to 1500 Ωm) and underlying weathered limestone (10 to 75 Ωm).…”
Section: Methodsmentioning
confidence: 79%
“…In addition to their field case study, Kwon et al [38] presented a numerical study evaluating the potential of underwater ERT surveys when using floating electrodes or electrodes placed at the bottom of the river bed with regards to electrode spacing, sensitivity and electrode spreads. Nyquist et al [39] used stream bottom ERT to map groundwater discharge and assess groundwater-surface water interaction within streams. They show that patterns of groundwater discharge can be mapped at the meter scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They develop an automated algorithm to extract the depth to bedrock using borehole and AEM data. There are a few engineering examples that demonstrate the capability of geophysical measurements, especially electric and electromagnetic (EM) methods, on lakes, rivers, or streams (e.g., Nyquist et al, 2008;Toran et al, 2010). Day-Lewis et al (2006) present results of two case studies that demonstrate the usage of continuous resistivity profiling for identifying the spatial distribution of submarine groundwater discharge and subbottom freshwater.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogeologic and environmental factors such as the water content, porosity, salinity, clay content, pore geometry, and pore-fluid temperature control the electrical resistivity of a medium (Everett, 2013). ERI surveys can be used to delineate 15 groundwater discharge areas (Nyquist et al, 2008), recharge pathways through mantled sinkholes (Schwartz and Schreiber, 2009), and riverbed sediment architecture (Crook et al, 2008). Daily et al (1992) showed that ERI can effectively map changes in water content within the vadose zone by analyzing the temporal changes in electrical resistivity as a result of an infiltration event.…”
mentioning
confidence: 99%